John Buchan’s amicable anti-modernism - Waddell, Nathan (Indiana University Press, 2012)
This article considers the novelist John Buchan’s changing responses to literary modernism in the inter-war period. It argues that although Buchan has generally been taken as a straightforward opponent of modernist writing, careful study of his oeuvre discloses a more complex scenario in which an antagonism to certain modernist 'excesses' is mixed with a qualified attraction to particular modernist innovations. The article’s central assumption is that a key part of Buchan’s worth to the New Modernist Studies lies in his querying — in novelistic as well as in essayistic forms — of the vocabularies now used to elaborate such literary-historical oppositions as high vs. low, for instance, or old vs. new. The article breaks new ground by moving beyond familiar Buchan texts — e.g. 'The Thirty-Nine Steps' (1915) — into the less appreciated territory of his novel 'Huntingtower' (1922), his literary criticism and his cultural commentaries.